2016
DOI: 10.17265/1539-8072/2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Studies on Bilingual Children’s Word Awareness Development

Abstract: Bilingual children's word awareness can reflect the impact of bilingualism on language cognition from the aspect of psycholinguistics. The current studies on bilingual children's word awareness both at home and abroad show that there exist quite opposite points of views: bilingual disadvantage and bilingual advantage. The interpretation mechanisms of interference effect, word frequency, and mutual exclusivity constraint are used to support the bilingual disadvantage; while the interpretation mechanisms of bili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Picture naming is affected by abilities other than articulation, including memory, visuospatial skills, vocabulary, visual perception, and lexical-semantic abilities (Yochim, Kane, & Mueller, 2009). Wen-Hui (2016) found that a picture-naming task slows the EL2 learner down and demonstrates a high rate of errors in this population. During a picture-naming task, EL2 learners produce words at a slower rate and therefore have reduced word output.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Picture naming is affected by abilities other than articulation, including memory, visuospatial skills, vocabulary, visual perception, and lexical-semantic abilities (Yochim, Kane, & Mueller, 2009). Wen-Hui (2016) found that a picture-naming task slows the EL2 learner down and demonstrates a high rate of errors in this population. During a picture-naming task, EL2 learners produce words at a slower rate and therefore have reduced word output.…”
Section: Introductionmentioning
confidence: 99%
“…If the sounds of the target words in the second language are similar to those of the first language, the ability to name pictures in the second language will be reduced (Hermans, Bongaerts, De Bot, & Schreuder, 1998; Lee & Williams, 2001). This phenomenon is referred to as cross-linguistic interference, which purports that the activation of the first language affects the processing of the second language (Wen-Hui, 2016). The disadvantage of word output can be attributed to this competition between the two languages (Gollan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation